STUDY ON SYNTHESIS AND CRYSTAL STRUCTURE OF TETRAKIS-(μ2-ACETATO)-DIHYDRATE-DICOPPER(II) - LI-HUA WANG (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
A new binuclear Cu(II) complex, tetrakis-(μ2-acetato)-dihydrate-dicopper (II), has been prepared by the reaction of Cu(OAc)2·H2O with 2-formyl-benzenesulfonate-hydrazine in the CH3CH2OH/H2O (v : v = 1 : 1). It was characterized by elemental analysis, IR and X-ray single crystal diffraction analysis. The crystal of the Cu(II) complex belongs to monoclinic, space group C2/c with a = 13.162(3) Å, b = 8.5572(17) Å, c = 13.860(3) Å, β = 117.06(3) º, V = 1390.1(5) Å3, Z = 4, Dc = 1.889 μg·m-3, μ = 3.103 mm-1, F(000) = 792, and final R1 = 0.0548, wR2 = 0.1410. Two Cu(II) centers are bridged by oxygen atoms of carboxylato groups. Each Cu(II) center is five-coordinated with four O donor atoms of acetate and a O donor of coordinated water molecule. The molecules form three dimensional network structures by the inaction of π-π stacking and hydrogen bonds.